Mixed‐Phase Clouds Over the Southern Ocean as Observed From Satellite and Surface Based Lidar and Radar. Issue 16 (11th August 2021) - Mace, Gerald G.; Protat, Alain; Benson, Sally
Abstract: This study investigates the occurrence of mixed‐phase clouds (MPC, i.e., cloud layers containing both liquid and ice water at sub‐freezing temperatures) over the Southern Ocean (SO) using space‐ and surface‐based lidar and radar observations. The occurrence of supercooled clouds is dominated by geometrically thin (<1 km) layers that rarely contain ice. We diagnose layers that are geometrically thicker than 1 km to contain ice 65% and 4% of the time from below by surface remote sensors and from above by orbiting remote sensors, respectively. We examine the discrepancy in MPC occurrence statistics as diagnosed from below and above the cloud layer. From above, we find that MPC occurrence has a gradient associated with the Antarctic Polar Front near 55°S with a rare occurrence of satellite‐derived MPC south of that latitude. In contrast, surface sensors find ice in 33% of supercooled liquid water layers. We infer using observing system simulation experiments and data analysis that space‐based lidar cannot identify the occurrence of MPC except when secondary ice‐forming processes operate in convection that is, sufficiently strong to loft ice crystals to cloud tops. We conclude that the CALIPSO phase statistics of MPC have a severe low bias in MPC occurrence. Based on surface‐based statistics in the SO, we present a parameterization of the frequency of MPC as a function of cloud top temperature that differs substantially from that used in recent climate model simulations. Plain Language Summary: The existence of snow in predominantly liquid clouds has important implications for the amount of sunlight absorbed mostly at the sea surface over the high latitude oceans. Particularly over the Southern Ocean, where satellite measurements suggest that ice concentrations are low, knowledge of how often clouds are snowing has critical climate implications. Observations from the surface have high fidelity in identifying snow below cold clouds. We use new measurements collected from Australian research vessels to establish an accurate survey of snow occurrence. We find that the occurrence of snow below cold clouds is much higher from ship observations than inferred from satellite. We explore reasons for this discrepancy and settle on an explanation that the low concentrations of ice‐nucleating aerosol particles result in low concentrations of ice particles except where convective motions are strong enough to create ice particles spontaneously by freezing large drops. We provide a simple temperature‐based parameterization of snow occurrence using surface‐based measurements for atmospheric models to use. Key Points: Lidar observations from above cloud layers significantly undercount the occurrence of mixed phase clouds over the Southern Ocean (SO) A latitudinal gradient in mixed‐phase clouds is found associated with the Antarctic Polar Front of the Antarctic Circumpolar Current Current parameterizations that modify the phase detrainment temperature of shallow convection are not supported by observations. An alternate parameterization developed from SO surface data is suggested